Inside Back Cover: Sequential Chiral Induction and Regulator‐Assisted Chiral Memory of Pillar[5]arenes (Angew. Chem. Int. Ed. 46/2020). Issue 46 (13th October 2020) - Fa, Shixin; Egami, Kouichi; Adachi, Keisuke; Kato, Kenichi; Ogoshi, Tomoki
Abstract : Chirality transfer is widely observed in life processes. In their Communication on page 20353, T. Ogoshi and co‐workers introduce a new non‐direct chiral transfer system, in which the chiral induction and memory processes occur within a single system via the synergistic interactions of a chiral regulator and inducer. The planar chirality of an acceptor is induced and memorized by a chiral inducer with precise control by a regulator. The memorization of the planar chirality of pillar[5]arenes by the regulator (net) is illustrated.